Implementation of "Freedom to Learn - Independent Campus": How prepared is English Department in higher education? - Susidamaiyanti; Wahyuningsih, Sungkawati Kardi (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2024)
This study aims to analyze the readiness of the Tadris Bahasa Inggris (TBI) program at IAIN Takengon to implement the Freedom to Learn - Independent Campus (FLIC) program. The research employs a descriptive survey method, with the study subjects consisting of 24 students and 14 lecturers from the TBI program at the Faculty of Tarbiyah, IAIN Takengon, selected purposively. Data were collected through questionnaires and interviews and then analyzed using quantitative techniques and qualitative thematic analysis for the interviews. The findings reveal that while the TBI program demonstrates substantial readiness, including implementing relevant activities, significant challenges remain, such as the need for adjustments in academic policies, funding, and curriculum alignment. The enthusiasm of both lecturers and students indicates promising potential for the successful implementation of FLIC. However, addressing the identified challenges will require holistic institutional support and the involvement of all stakeholders. This study contributes to the understanding of institutional readiness for innovative educational policies and offers concrete recommendations for optimizing the implementation of FLIC in similar programs.